Rapid Detection of New Delhi Metallo-β-Lactamase Gene Using Recombinase-Aided Amplification Directly on Clinical Samples From Children - Feng, Yanling; Xue, Guanhua; Feng, Junxia; Yan, Chao; Cui, Jinghua; Gan, Lin; Zhang, Rui; Zhao, Hanqin; Xu, Wenjian; Li, Nannan; Liu, Shiyu; Du, Shuheng; et al. (Frontiers in Microbiology, 2021)
New Delhi metallo-β-lactamase, a metallo-β-lactamase carbapenemase type, mediates resistance to most β-lactam antibiotics including penicillins, cephalosporins, and carbapenems. The detection rate of this gene in children’s samples is higher than in adults. Therefore, it is important to detect blaNDM genes in children’s clinical samples as quickly as possible and analyze their characteristics. Here, a recombinase-aided amplification (RAA) assay, which operates in a single one-step reaction tube at 39°C in 5−15 min, was established to target blaNDM genes in children’s clinical samples. The analytical sensitivity of the RAA assay was 20 copies, and the various bacterial types without blaNDM genes did not amplify. This method was used to detect blaNDM genes in 112 children’s stool samples, 10 of which were tested positive by both RAA and standard PCR. To further investigate the characteristics of carbapenem-resistant bacteria carrying blaNDM in children, 15 carbapenem-resistant bacteria (Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, Citrobacter freundii, KlebsiellaK. oxytoca, AcinetobacterA. junii, and Proteus mirabilis) were isolated from the 10 samples. Notably, more than one bacterial type was isolated from three samples. Most of these isolates were resistant to cephalosporins, cefoperazone-sulbactam, piperacillin-tazobactam, ticarcillin-clavulanic acid, aztreonam, co-trimoxazole, and carbapenems. blaNDM-1 and blaNDM-5 were the two main types in these samples. These data show that the RAA assay has potential to be a sensitive and rapid blaNDM gene screening test for clinical samples. The common existence of blaNDM and multi-drug resistance genes presents major challenges for pediatric treatment.